2007
DOI: 10.1016/j.bbrc.2007.06.136
|View full text |Cite
|
Sign up to set email alerts
|

Food entrainment of circadian gene expression altered in PPARα−/− brown fat and heart

Abstract: The circadian clock is subject to food entrainment. Since PPARalpha exhibits a circadian expression profile, we hypothesized that PPARalpha deficiency would alter the food entrainable response of adipose, cardiac, and liver tissues. Wild-type and PPARalpha null mice were compared under ad libitum or restricted food access for the expression of circadian transcription factor-encoding mRNAs. Temporally restricted food access caused between a mean 5.8-11.5 h phase shift in the expression profiles of the circadian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…In addition, PPAR␣ plays a role in the entrainment by food of peripheral pacemakers. 47 These data indicate that the clock components and nuclear receptors integrate signals from both intermediary metabolism and the circadian clock to optimize fuel use or storage across the light/dark cycle.…”
Section: Circadian Control Of Energy Homeostasis Circadian Control Ofmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, PPAR␣ plays a role in the entrainment by food of peripheral pacemakers. 47 These data indicate that the clock components and nuclear receptors integrate signals from both intermediary metabolism and the circadian clock to optimize fuel use or storage across the light/dark cycle.…”
Section: Circadian Control Of Energy Homeostasis Circadian Control Ofmentioning
confidence: 94%
“…68 PPAR␣ is also necessary for food entrainment of the clock in the mouse heart. 47 Altered cardiac fatty acid use and cardiac function may result from perturbed circadian PPAR␣ signaling.…”
Section: Clock Genes and Nuclear Receptors Control The Circadian Contmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor a (PPARa), a nuclear receptor family member, provides an example of coordination between circadian and metabolic processes (11). It has been shown that CLOCK/ BMAL1-mediated transcription of period (PER) and cryptochrome (CRY) is modulated by PPARa/RXRa, which suggests that there may be crosstalk between PPARa/RXRa-and CLOCK/ BMAL1-regulated systems and lipid metabolism (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Using a Per1::luciferase transgenic construct as a reporter, Stokkan et al [10] also demonstrated that changes in metabolic cycles can shift the phase of clock oscillation in the hepatic tissue, which persists even after the tissue is excised from the body. Furthermore, even in cardiovascular tissues, as well as in metabolic tissues, the timing of energy intake can affect the cyclic expression of clock genes [12][13][14], indicating that energy metabolism is an important modulator of clock function in cardiovascular tissues.…”
Section: Nuclear Receptors Link Circadian and Metabolic Functionsmentioning
confidence: 99%
“…For example, the phase of clock oscillation in metabolic tissues such as the liver and fat tissue is reset by alterations in the timing of energy intake [10,11]. Furthermore, even in cardiovascular tissues, including the heart and aorta, the molecular clock can sense temporal changes in energy metabolism [12][13][14]. This recognition has broadened our view of how the internal circadian system integrates multiple stimuli from the external world to organize physiological rhythms, including the 24-hour blood-pressure rhythm.…”
mentioning
confidence: 99%